Pendekatan Keterampilan Dalam Pembelajaran Bahasa Arab - Muna Nabila Amatullah; Novi Kusumaningrum (An Nabighoh Jurnal Pendidikan Dan Pembelajaran Bahasa Arab, 2020)
The approach is an essential part of language teaching. This is a way of looking at teaching and learning. One of the techniques of Arabic language teaching is the Integrated Skills Approach. This approach combines four language skills in the learning process. This study aims to describe the mastery approach and its implementation in learning Arabic. The method used in this research is a descriptive qualitative method. The data in this study were collected through library research. Based on the study results, it was found that using the integrated skills approach in learning Arabic will train students in the use of language in its entirety and naturally, which includes receptive and productive language activities. Because in real life these four skills are not used separately.